Eleições em São Paulo do século XIX: uma pletora de leis, votantes e votos em disputa (Ágora Journal, 2020)
This article will attempt to approach, in the context of the province of São Paulo in the second half of the nineteenth century, some aspects of the problem of elections in Brazil Empire, moving away from the perspective of “institutional falsification”. On the one hand, the electoral laws and successive regulations of the imperial government were mobilized and disputed by local parties agents, who sought to control key posts at the electoral tables that organized and held the elections. On the other hand, voters and their votes, whose meanings were very different from current ones, were actively disputed by those same agents, at the same time that they could be active participants in these disputes, provided that they channeled their wishes and sought to negotiate their participation within the networks that constituted the electoral forces in each locality.